Teaching Triangles: A Campus Wide Interdisciplinary Program for Faculty Professional Development - Gwen Landever; Caroline Mackintosh (The Advocate, 2016)
Providing meaningful professional development at a small teaching university can be a challenge. Since there are limited opportunities to bring in big named speakers for a lecture or to send faculty to conferences, faculty and administration need to find low cost and creative ways to support professional development. This paper will discuss how a university has transformed faculty development through a peer-based model called “Teaching Triangles”. Initially adopted as a method to support new faculty in one department, it has grown into an interdisciplinary campus wide initiative. Along with faculty participation, students have also become actively involved in the process.